2015
DOI: 10.4141/cjps2013-324
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen allocation in barley: Relationships between amino acid transport and storage protein synthesis during grain filling

Abstract: Egle, K., Beschow, H. and Merbach, W. 2015. Nitrogen allocation in barley: Relationships between amino acid transport and storage protein synthesis during grain filling. Can. J. Plant Sci. 95: 451Á459. A better knowledge of the source-sink relationships relating to nitrogen allocation within plant and synthesis of storage protein in grains could be of particular importance contributing to better define grain sink capacity for improving nitrogen use efficiency by plant species. The objectives of this study were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
(41 reference statements)
1
4
0
Order By: Relevance
“…It is hypothesized that the negative correlation between the two traits result when the high demand for N during seed filling stage coincides with decline in soil nutrients in the rhizosphere and nitrogen fixation, resulting in re-mobilization of nitrogen from leaves, which in turn shortens grain filling and reduces seed weights 86 . This is in line with findings by Egle, et al 87 who showed that majority of N accumulated during seed filling in barley was remobilized from leaves and stems, but that ongoing N uptake could also contribute. Furthermore, wheat genotypes with higher capability for post-anthesis N uptake deviate from grain-protein negative relationship [88][89] and selection for this trait has been therefore proposed as a possible criterion for simultaneous improvement of protein content and grain yield.…”
Section: Uncoupling the Negative Yield-protein Correlationsupporting
confidence: 93%
“…It is hypothesized that the negative correlation between the two traits result when the high demand for N during seed filling stage coincides with decline in soil nutrients in the rhizosphere and nitrogen fixation, resulting in re-mobilization of nitrogen from leaves, which in turn shortens grain filling and reduces seed weights 86 . This is in line with findings by Egle, et al 87 who showed that majority of N accumulated during seed filling in barley was remobilized from leaves and stems, but that ongoing N uptake could also contribute. Furthermore, wheat genotypes with higher capability for post-anthesis N uptake deviate from grain-protein negative relationship [88][89] and selection for this trait has been therefore proposed as a possible criterion for simultaneous improvement of protein content and grain yield.…”
Section: Uncoupling the Negative Yield-protein Correlationsupporting
confidence: 93%
“…Carbon and nitrogen contents in roots and shoots were determined from 10 mg of ground samples using a C/N analyser (Vario EL, Elemental Analysis System, Hanau, Germany) at Martin‐Luther‐University following Egle, Beschow, and Merbach ().…”
Section: Methodsmentioning
confidence: 99%
“…TKW is also affected by grain shape and size (Su et al 2018). These characteristics are determined by the temporal and spatial regulation of cell division, cell expansion, and the duration and rate of grain filling (Wheeler et al 1996;Drea et al 2005;Pielot et al 2015;, which are dependent on the availability and acquisition of essential resources (Weber et al 1998;Yang et al 2004;Lopes et al 2006;Egle et al 2015;Weichert et al 2017). We note that grain development in wheat spikelets follows an acropetal order (Kirby 1974;Whingwiri and Stern 1982), showing a decrease in grain weight or dry matter accumulation acropetally within the spikelets (Rawson and Evans 1970;Kirby 1974;Whingwiri et al 1981;.…”
Section: Grain Development and Dry Matter Accumulation In Fl-bh T -A1mentioning
confidence: 88%